EIGENVALUES AND EIGENFUNCTIONS OF DISCONTINUOUS TWO-POINT BOUNDARY VALUE PROBLEMS WITH AN EIGENPARAMETER IN THE BOUNDARY CONDITION - Caliskan, S.; Bayramov, A.; Oer, Z.; Uslu, S. (ROCKY MT MATH CONSORTIUM, 2013)
In this paper we get asymptotic formulas for eigenvalues and eigenfunctions of discontinuous two-point boundary value problems with the eigenparameter in the boundary conditions with transmission conditions at the two points of discontinuity. When our problem is continuous the obtained results coincide with the corresponding results in [3].
Keywords: Two-point boundary value problems; transmission condition; asymptotic of eigenvalues and eigenfunctions; discontinuous boundary value problems; PARAMETER; Mathematics